The Sense of 1PP-Location Contributes to Shaping the Perceived Self-location Together with the Sense of Body-Location - Huang, Hsu-Chia; Lee, Yen-Tung; Chen, Wen-Yeo; Liang, Caleb (Frontiers in Psychology, 2017)
Self-location—the sense of where I am in space—provides an experiential anchor for one’s interaction with the environment. In the studies of full-body illusions, many researchers have defined self-location solely in terms of body-location—the subjective feeling of where my body is. Although this view is useful, there is an issue regarding whether it can fully accommodate the role of 1PP-location—the sense of where my first-person perspective is located in space. In this study, we investigate self-location by comparing body-location and 1PP-location: using a head-mounted display (HMD) and a stereo camera, the subjects watched their own body standing in front of them and received tactile stimulations. We manipulated their senses of body-location and 1PP-location in three different conditions: the participants standing still (Basic condition), asking them to move forward (Walking condition), and swiftly moving the stereo camera away from their body (Visual condition). In the Walking condition, the participants watched their body moving away from their 1PP. In the Visual condition, the scene seen via the HMD was systematically receding. Our data show that, under different manipulations of movement, the spatial unity between 1PP-location and body-location can be temporarily interrupted. Interestingly, we also observed a “double-body effect”. We further suggest that it is better to consider body-location and 1PP-location as interrelated but distinct factors that jointly support the sense of self-location.